Metabolomic and transcriptomic analyses jointly reveal the mechanism underlying the reddening of Chimonanthus praecox stamens - Liu, Bin; Wu, Huafeng; Cao, Yinzhu; Ma, Guanpeng; Zheng, Xiaowen; Zhu, Haoxiang; Song, Xingrong; Sui, Shunzhao (Frontiers in Plant Science, 2024)
Chimonanthus praecox. Over its long cultivation history, variations have been observed in the floral organs, primarily in the petals, with limited reports on stamen traits. Stamen variation, integral to the mating system, can enhance the plant's ornamental value and directly impact its reproductive success. This study is the first to report the phenomenon of red coloration in C. praecox stamens. Using UPLC-MS/MS, we analyzed the types and quantities of major metabolites in stamens of different colors. Our results indicated that the red coloration was primarily due to the accumulation of high levels of anthocyanins, specifically cyanidin 3-O-rutinoside and cyanidin 3-O-glucoside.Transcriptomic sequencing identified 63 differentially expressed genes (DEGs) related to the anthocyanin biosynthetic pathway, most showing peak expression during the bud stage. The results of the metabolite analysis and transcriptomic sequencing were similar to those of previous studies on petal reddening, suggesting a close relationship between the mechanisms of stamen and petal reddening. This study elucidated the mechanism of stamen reddening in C. praecox, expanding the species' genetic resources and offering insights into color changes across floral tissue.